Functional gait assessment after wide tumor resection and knee endoprosthesis reconstruction: a retrospective cross-sectional study - Bhatnagar, Rachit; Deshwal, Sidharth; Gautam, Vivek Kumar (International Journal of Research in Orthopaedics, 2026)
Background: Limb salvage surgery with endoprosthetic reconstruction around the knee is widely performed for primary malignant bone tumors and aggressive giant cell tumors. Although oncological control is well established, objective evaluation of postoperative gait and its correlation with functional outcome remains limited. This study aimed to assess gait pattern and functional outcome following wide tumor resection and knee endoprosthesis reconstruction. Methods: This retrospective cross-sectional study included 20 patients who underwent wide resection and endoprosthesis reconstruction around the knee. Patients were evaluated at a minimum of six months postoperatively. Functional outcome was assessed using the musculoskeletal tumor society (MSTS) scoring system. Three-dimensional gait analysis was performed using a motion capture system based on the Helen Hayes protocol to measure walking velocity, stride length, stance phase, and knee range of motion. Statistical analysis was performed using appropriate parametric tests, with p<0.05 considered significant. Results: The mean MSTS score was 22.95 out of 30, indicating good to excellent functional outcome in 90% of patients. The mean walking velocity was 0.92 m/s, representing a 31.31% reduction compared to normal reference values. Stride length and walking velocity were significantly reduced compared to normative data (p<0.001). Sixteen patients (80%) demonstrated a stiff knee gait, while two (10%) exhibited a flexed knee gait. Patients with distal femur reconstruction showed better functional outcomes than those with proximal tibia involvement. Conclusions: Knee endoprosthesis reconstruction following tumor resection provides satisfactory functional outcomes despite measurable alterations in gait parameters. Objective gait analysis is a valuable tool for assessing postoperative functional recovery.